Impact of digital government construction on the intelligent transformation of enterprises: Evidence from China - Zhang, Longpeng; Zhang, Xingye (Technological forecasting & social change, 2025)
In the digital age, driving the intelligent transformation of enterprises is a crucial research topic. This study examines the impact of digital government development on enterprise transformation and explores the pathways to achieve it. Drawing from digital governance and institutional economics theories, government data openness, cloud platform construction, and intelligent government services provide a favorable external environment for enterprise transformation. Digital government development also reduces institutional transaction costs, thus enabling enterprises to invest more resources in technological innovation, including artificial intelligence applications. Empirical research on Chinese listed firms supports these findings. Furthermore, the construction of digital government can effectively promote innovation and management intelligence within the internal value chain of enterprises. Other heterogeneity analyses indicate that this effect is more pronounced in technology-intensive industries and developed regions. •Digital government provides a favorable external environment for enterprise intelligence.•Digital government promotes enterprise intelligence by reducing the institutional transaction costs.•Digital government can effectively promote enterprise innovation and management intelligence.•Enterprises in developed region and technology industries are impacted more significantly by digital government.